Prevalence of extended‐spectrum β‐lactamase‐producing Enterobacteriaceae in humans living in municipalities with high and low broiler density. (11th February 2013) - Huijbers, P. M. C.; de, M.; Graat, E. A. M.; van, A. H. A. M.; van, M. G.; de, M. C. M.; van, E.; de, S. C.; Cantón, R.
Abstract Prevalence of, and risk factors for, carriage of extended‐spectrum β‐lactamase (ESBL) ‐producing Enterobacteriaceae were determined for 1025 Dutch adults in municipalities with either high or low broiler densities. Overall prevalence of ESBL carriage was 5.1%. The hypothesis that individuals in areas with high broiler densities are at greater risk for ESBL carriage was rejected, as the risk was lower (OR = 0.45; p 0.009) for these individuals. Owning a horse increased the risk (OR = 4.69; p ≤0.0001), but horse owners often owned multiple species of companion animals. Routes of transmission from animals to humans in the community, and the role of poultry in this process, remain to be elucidated.